USE OF IPSS-QOL IN ASSESSING SYMPTOMS AND QUALITY OF LIFE IN PATIENTS WITH STRICTURAL URETHRAL DISEASES IN MEN - Rakhmonberdiev Kh. K.; Navruzov E. R. (Galaxy International Interdisciplinary Research Journal, 2023)
To assess symptoms and quality of life in men with urethral strictures,the IPSS-QoL questionnaire is used. Testing the psychometric properties of the questionnaire for this category patients were not carried out.